Identification of DNA Recognition Sequences and Protein Interaction Domains of the Multiple-Zn-Finger Protein Roaz - Tsai, Robert Y. L. (American Society for Microbiology, 1998)
Roaz, a rat C(2)H(2) zinc finger protein, plays a role in the regulation of olfactory neuronal differentiation through its interaction with the Olf-1/EBF transcription factor family. An additional role for the Roaz/Olf-1/EBF heterodimeric protein is suggested by its ability to regulate gene activation at a distinct promoter lacking Olf-1/EBF-binding sites. Using an in vitro binding-site selection assay (Selex), we demonstrate that Roaz protein binds to novel inverted perfect or imperfect repeats of GCACCC separated by 2 bp. We show that Roaz is capable of binding to a canonical consensus recognition sequence with high affinity (K(d) = 3 nM). Analysis of the structural requirement for protein dimerization and DNA binding by Roaz reveals the role of specific zinc finger motifs in the Roaz protein for homodimerization and heterodimerization with the Olf-1/EBF transcription factor. The DNA-binding domain of Roaz is mapped to the N-terminal 277 amino acids, containing the first seven zinc finger motifs, which confers weak monomeric binding to a single half site and a stronger dimeric binding to the inverted repeat in a binding-site-dependent manner. Full-length protein can form dimers on both the inverted repeat and direct repeat but not on a single half site. These findings support the role of the TFIIIA-type Zn fingers in both protein-protein interaction and protein-DNA interaction and suggest distinct functions for specific motifs in proteins with a large number of zinc finger structures.